Geochemical characterisation of Antarctic soils and lacustrine sediments from Terra Nova Bay - MALANDRINO, Mery; ABOLLINO, Ornella; BUOSO, Sandro; C. E. Casalino; M. Gasparon; GIACOMINO, AGNESE; LA GIOIA, Carmela; MENTASTI, Edoardo (Microchemical Journal, 2009)
In Terra Nova Bay region (northern Victoria Land, Antarctica), the interactions among soil, meltwater and lakes are poorly understood with regard to the physicochemical transformations that occur when solid materials are exchanged among them. In order to ascertain the natural dynamics of several elements, namely Al, As, Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, P, Pb, Ti and Zn, as well as the perturbations by human activities and/or global contamination, soils and sediments from four catchments (Tarn Flat, Edmonson Point, Inexpressible Island and Northern Foothills) were studied. To accomplish the above mentioned objectives, the particle-size distribution and mineralogical composition, as well as the total C, H and N contents and the total concentrations of the investigated elements were determined. Finally in order to assess metal mobility, the modified BCR three-step sequential extraction procedure was applied to the samples and the partitioning of five metals, namely Cr, Fe, Mn, Pb and Zn, into different fractions was determined. Lithology and topography are the main factors that differentiate the physicochemical characteristics of the soils and sediments investigated. The lacustrine sediments and the soils sampled around the lakes showed a similar mineralogical and chemical composition, as evidence that rock- and soil-weathering processes occur primarily during the warm summer periods, when the lakes are partially ice-free. Nevertheless the presence of chlorite in these systems indicated that chemical weathering has taken place even in these extreme conditions. In general, the geochemical composition of soils and sediments in this Antarctic area seems to be influenced mainly by the nature of the bedrock and by the input of sea-spray, and, to a lesser degree, by mechanical and chemical weathering as well as by biological processes; no evidence of a local or global anthropogenic contamination was found.